2020
DOI: 10.1002/bco2.47
|View full text |Cite
|
Sign up to set email alerts
|

Transition zone prostate cancer is associated with better clinical outcomes than peripheral zone cancer

Abstract: The incidence of prostate cancer (PCa) has dramatically increased since the introduction of prostate-specific antigen (PSA) screening in the late 1980s. Significant variations have been reported for the incidence of PCa between races and regions. For instance, Asian countries are known to have a low incidence, which is onetenth compared to the highest incidence in European countries, 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…The other two studies, which patient cohorts were based in Asia, had no further validation studies to prove the efficacy of the developed nomogram 174,176 [H1] Clinical outcomes -the influence of prostate zones Results of several studies have shown an association between tumour zone of origin and clinical outcome, as well as multiple clinical prognostic parameters (Table 2). In general, in all the studies that reported clinical outcome, that is, biochemical relapse-free survival, metastasis-free survival or prostate cancer-related death, outcome was better for patients diagnosed with TZ tumours than with PZ tumours 11,12,33,34,36,41,58,178,179 . Higher proportions of TZ tumours in prostatectomy specimens from Japanese men (34-46%) was shown in two studies 12,33 compared with studies done in Western countries (10-25%) 11,38,41,42,180 .…”
Section: [H2] Treatment Decision-making -Zonal Agnosticmentioning
confidence: 98%
See 2 more Smart Citations
“…The other two studies, which patient cohorts were based in Asia, had no further validation studies to prove the efficacy of the developed nomogram 174,176 [H1] Clinical outcomes -the influence of prostate zones Results of several studies have shown an association between tumour zone of origin and clinical outcome, as well as multiple clinical prognostic parameters (Table 2). In general, in all the studies that reported clinical outcome, that is, biochemical relapse-free survival, metastasis-free survival or prostate cancer-related death, outcome was better for patients diagnosed with TZ tumours than with PZ tumours 11,12,33,34,36,41,58,178,179 . Higher proportions of TZ tumours in prostatectomy specimens from Japanese men (34-46%) was shown in two studies 12,33 compared with studies done in Western countries (10-25%) 11,38,41,42,180 .…”
Section: [H2] Treatment Decision-making -Zonal Agnosticmentioning
confidence: 98%
“…The prostate zones were defined more than half a century ago, and an appreciation of the clinical implication of tumour location has been increasing with evidence from mostly retrospective studies. In general, patients with TZ tumours tend to have a better prognosis than those with PZ tumours 11,12,[33][34][35][36][37][38][39][40][41][42] . However, the zonal origin of the tumour has not been integrated into the treatment decision-making process owing to the lack of prospective studies and limited understanding of tumour biology.…”
Section: [H1] Current Care: a Zone-independent Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…They focused on socioeconomic status as a predictor of survival but could also show relationships with modifiable risk factors such as treatment delays. A hint for future authors—this authorship group has an open access agreement in place that covers article publication charges—be sure to check the Wiley website to see if your institution has one (see our web page and follow the links to Wiley Open Access). To the Clinic … We have three clinical utility papers for your interest—focused efforts on prostate cancer pathology correlates to outcomes, 3 a practical study asking the question as to whether or not the prostate screening digital rectal exam matters any more when PSA and MRI are known, 4 and a detailed comparison of MRI accuracy metrics judged by radical prostatectomy findings across different anatomic zones 5 . This latter paper is useful in that anterior lesions had lower sensitivity for MRI, but the authors do question whether negative findings need additional corroboration (biopsy, other imaging, etc). To the Drawing Board … We have two papers in this section.…”
Section: Figurementioning
confidence: 99%
“…To the Clinic … We have three clinical utility papers for your interest—focused efforts on prostate cancer pathology correlates to outcomes, 3 a practical study asking the question as to whether or not the prostate screening digital rectal exam matters any more when PSA and MRI are known, 4 and a detailed comparison of MRI accuracy metrics judged by radical prostatectomy findings across different anatomic zones. 5 This latter paper is useful in that anterior lesions had lower sensitivity for MRI, but the authors do question whether negative findings need additional corroboration (biopsy, other imaging, etc).…”
mentioning
confidence: 99%